DEVELOPMENT PROCESS OF TRADITIONAL CRAFT INDUSTRY IN UNGGAN VILLAGE, WEST SUMATRA PROVINCE, INDONESIA - , Vita Lusiana Putri; , Ir. Agam Marsoyo, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The local government of Sijunjung regency has provided advisory programs such as clustering program, exhibitions and trainings for development of Unggan woven fabric industry but it seems all of these programs still not ensure the sustainability of Unggan woven fabric industry because it is not pay much attention to the capabilities and craftsmanship skills of each weaver and less considering the context and needs of Unggan weavers. This study aimed to proposes alternative startegy to develop Unggan woven fabric industry, which are collaborative strategy and innovation strategy, and also suggestions to improve the program that has been implemented, which is clustering. Unggan village already announced by the government as woven fabrics industry cluster but in fact this cluster not yet well-developed especially in external networks such aslinks to the banks and other financial institutions, suppliers of inputs, traders or crafts store owners, and other supporting institutions (universities, large enterprises, designer association). Collaborative approach is one of alternative ways that can be used to build external networks of Unggan woven fabric industry cluster. By considering the capability andcraftsmanship skill of each weaver and combine them with other parties capabilities in collaborative work is expected can generate some ideas for new products, ideas for how to expose the unique character of Unggan woven fabric and ideas to find the potentials target market. There are alternative parties that could work collaboratively with the Ungganweavers in the future to ensure the development and sustainability of Unggan Woven fabrics industry, such asIndonesian Fashion Designers Association of West Sumatera,craft retailers or storeowners in big cities at West Sumatera province, and collaboration with colleges/universities. Ungganweavers can use either market-driven or identity-driven strategy, or a mixture of them for innovation strategy.Innovations could be in terms of design motifs, design products and innovation of materials used.